Leptin/adiponectin ratio predicts poststroke neurological outcome. (19th October 2015) - Carbone, Federico; Burger, Fabienne; Roversi, Gloria; Tamborino, Carmine; Casetta, Ilaria; Seraceni, Silva; Trentini, Alessandro; Padroni, Marina; Bertolotto, Maria; Dallegri, Franco; Mach, François; Fainardi, Enrico; et al.
Abstract Background and aims Different adipokines have been associated with atherosclerotic plaque rupture and cardiovascular events, such as acute ischaemic stroke (AIS). However, the potential role of these molecules in postischaemic brain injury remains largely unknown. Methods and methods We performed a substudy analysis on nonobese patients with first atherothrombotic stroke (n = 35) from a recently published prospective cohort. Primary endpoint was to investigate the predictive value of serum leptin/adiponectin ratio on neurological recovery at 90 days after AIS. The secondary endpoint was the predictive value of serum adipokine levels of clinical and radiological outcomes at a shorter follow‐up (at days 1 and 7 after AIS). The radiological evaluation included ischaemic lesion volume and haemorrhagic transformation (HT). The clinical examination was based on National Institutes of Health Stroke Scale (NIHSS) and modified Rankin Scale (mRS). Results At day 1 after AIS, serum leptin and leptin/adiponectin ratio were increased and inversely correlated with both radiological and clinical parameters at all follow‐up time points. Once identified the best cut‐off points by receiver operating characteristic (ROC) analysis, risk analysis showed that higher circulating leptin improved neurological recovery at day 90. In addition, leptin/adiponectin ratio maintained statistical significance after adjustment for age, gender and thrombolysis, also predicting the occurrence of HT in the first 7 days after AIS (adjusted OR 0·15 [95% CI 0·03–0·83); P = 0·030]). Conclusions Higher leptin/adiponectin ratio at day 1 predicted better neurological outcomes in patients with atherothrombotic AIS and might be potentially useful as a prognostic biomarker of the disease.